CHET TILLARINI O’RGANISHDA YOSHLARDA PAYDO BO’LAYOTGAN STRESS VA DEPRESSIYA: UNING SABAB VA YECHIMLARI - Nurillayeva Muazzamoy; Nabiyeva Gulbahor (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the issues of stress and depression that arise among youth during the process of learning foreign languages. It examines the impact of psychological pressure in language learning, assessment systems, and the high expectations of parents and society on the mental health of young people. Furthermore, the article highlights the main causes of these issues and offers recommendations for overcoming them. This research is of great importance for students learning foreign languages, as well as for teachers and parents, as it can support their efforts in creating a healthy psychological environment for youth.